229th ENMC international workshop: Limb girdle muscular dystrophies – Nomenclature and reformed classification Naarden, the Netherlands, 17–19 March 2017 - Straub, Volker; Murphy, Alexander; Udd, Bjarne; Corrado, Angelini; Aymé, Ségolène; Bönneman, Carsten; de Visser, Marianne; Hamosh, Ada; Jacobs, Laura; Khizanishvili, Nina; Kroneman, Madelon; Laflorêt, Pascal; et al. (Neuromuscular disorders : NMD, 2018)
•A consensus was reached on an updated definition of LGMD, and current sub-types were evaluated by application of the updated definition.•Consensus was reached on the most useful LGMD classification system that also allowed space for further discoveries of new sub-types.•Potential ramifications of the new definition and classification of LGMD for patients were discussed and several action points around how to disseminate this proposal were identified.